Materials Processing for Production of Nanostructured Thin Films - Stine, Keith J. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Thin films are important in many of the technologies used every day, impacting major markets for energy, medicine, and coatings. Scientists and engineers have been producing thin films on a wide range of surfaces for many decades but now have begun to explore giving these films new and controlled structures at the nanometer scale. These efforts are part of the new horizons opened by the field of nanoscience and impart novel structures and properties to these thin films. This book covers some of the methods for making these nanostructured thin films and their applications in areas impacting on health and energy usage.